Effect of Financial Literacy and Learning Achievement on Student Consumptive Behaviour - Suparno Suparno; Ari Saptono; Agus Wibowo; Nabiya Putri (AL-ISHLAH: Jurnal Pendidikan, 2022)
The goal of this study was to ascertain how economic literacy and learning outcomes affected consumption. The research method employed quantitative surveys. The population of this study consisted of 686 students from SMAN 30 Jakarta, with 145 students from class XI IIS being the affordable population. Stratified Proportional Sampling Technique 101 respondents were counted by random sampling. The study used tests, questionnaires, and documentation as its sample methods. The data had a linear connection and was normally distributed, according to the analysis requirements test. The tolerance from economic literacy and economic learning result of the multicollinearity test is 0.538 0.01 based on the classical assumption test, and the VIF value is 1.85910. This study found that economic learning results and economic literacy had a significant detrimental impact on high school students' consumption behavior.